Gibberellins control Arabidopsis hypocotyl growth via regulation of cellular elongation - Cowling, R; Harberd, N (1999)
The gibberellins (GAs) are endogenous regulators of plant growth. Experiments are described here that test the hypothesis that GA regulates hypocotyl growth by altering the extent of hypocotyl cell elongation. These experiments use GA-deficient and altered GA-response mutants of Arabidopsis thaliana (L.) Heyhn. It is shown that GA regulates elongation, in both light- and dark-grown hypocotyls, by influencing the rate and final extent of cellular elongation. However, light- and dark-grown hypocotyls exhibit markedly different GA dose-response relationships. The length of dark-grown hypocotyls is relatively unaffected by exogenous GA, whilst light-grown hypocotyl length is significantly increased by exogenous GA. Further analysis suggests that GA control of hypocotyl length is close to saturation in dark-grown hypocotyls, but not in light-grown hypocotyls. The results show that a large range of possible hypocotyl lengths is achieved via dose-dependent GA-regulated alterations in the degree of elongation of individual hypocotyl cells.